LINC02282 promotes DNA methylation of TRIM6 by recruiting DNMTs to inhibit the progression of Parkinson's disease - Lu Han; Chuansheng Zhao; Feng Jin; Rongfeng Jiang; Hao Wu (Brain Research Bulletin)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. Long non-coding RNAs (lncRNAs) are closely linked to the occurrence and development of neurodegenerative diseases, while the underlying mechanisms remain elusive. The goal of the present study was to elucidate the mechanism by which LINC02282, a significantly downregulated lncRNA in the GEO database, elicits neuroprotective effects on PD. LINC02282 was poorly expressed in SH-SY5Y and SK-N-AS cells exposed to MPP+ and mice injected with MPTP. LINC02282 overexpression plasmids inhibited apoptosis and promoted the proliferation of SH-SY5Y and SK-N-AS cells. In addition, LINC02282 overexpression using an adeno-associated virus reduced neuronal damage in PD mice. LINC02282 was mainly localized in the nucleus, and LINC02282 promoted the methylation of the tripartite motif-containing protein 6 (TRIM6) promoter to inhibit TRIM6 expression. LINC02282 bound to DNA methyltransferases (DNMTs) and LINC02282 overexpression increased the binding of DNMTs to the TRIM6 promoter. Overexpression of TRIM6 alone induced PD-like symptoms in mice and combined TRIM6 upregulation inhibited the neuroprotective effect of LINC02282 both in vitro and in vivo. In summary, LINC02282 alleviated neuronal injury in PD by recruiting DNMTs to the promoter region of TRIM6 and inhibiting TRIM6 expression.